Phylogenetics of family Enterobacteriaceae and proposal to reclassify Escherichia hermannii and Salmonella subterranea as Atlantibacter hermannii and Atlantibacter subterranea gen. nov., comb. nov. (May 2016) - Hata, Hiroyuki; Natori, Tatsuya; Mizuno, Takuya; Kanazawa, Izumi; Eldesouky, Ibrahim; Hayashi, Masahiro; Miyata, Machiko; Fukunaga, Hajime; Ohji, Shoko; Hosoyama, Akira; Aono, Eiji; Yamazoe, Atsushi; et al.
ABSTRACT: Multilocus sequence analysis based on hypervariable housekeeping proteins was utilized to differentiate closely related species in the family Enterobacteriaceae . Of 150 housekeeping proteins, the top 10 hypervariable proteins were selected and concatenated to obtain distance data. Distances between concatenated proteins within the family were 0.9–41.2%, whereas the 16S rRNA and atpD‐gyrB‐infB‐rpoB concatenated sequence (4MLSA) distances were 0.8–6.0% and 0.9–22.1%, respectively. These data indicate that phylogenetic analysis by concatenation of hypervariable proteins is a powerful tool for discriminating species in the family Enterobacteriaceae . To confirm the discriminatory power of the 10 chosen concatenated hypervariable proteins (C10HKP), phylogenetic trees based on C10HKP, 4MLSA, and the 16S rRNA gene were constructed. Comparison of average bootstrap values among C10HKP, 4MLSA and 16S rRNA genes indicated that the C10HKP tree was the most reliable. Location via the C10HKP tree was consistent with existing assignments for almost all species in the family Enterobacteriaceae . However, the C10HKP tree suggested that several species (including Enterobacter massiliensis, Escherichia vulneris, Escherichia hermannii, and Salmonella subterranea ) should be reassigned to different clusters than those defined in previous analyses. Furthermore, E. hermannii and S. subterranea appeared to fall onto a branch independent from those occupied by the other Enterobacteriaceae . Therefore, we propose Atlantibacter gen. nov., such that E. hermannii and S. subterranea would be transferred to genus Atlantibacter as Atlantibacter hermannii, comb. nov. and Atlantibacter subterranea . comb. nov., respectively.